Experimental and Analytical Investigation of Mooring Angle and Tube Mass Effects on the Dynamic Response of a Submerged Floating Tunnel Segment Model under Wave Excitation - Akmal, Jamiatul; Dinata, Ragil Alvin; Tanti, Novri; Hasymi, Zulhendri; Nugraha, Nurcahya (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2026)
The Submerged Floating Tunnel (SFT) is an alternative infrastructure for crossing transportation routes in deep and wide waters, but further studies are still needed on the dynamic response to wave forces. This study aims to evaluate the dynamic response of a wave-excited Tension Leg type SFT segment model, specifically regarding the influence of the mooring cable angle and the influence of the tube mass. This study was conducted using a damped forced vibration theory approach, exploring the relationship among three main elements of structural dynamics: mass (?), damping (?), and stiffness (?). These parameters are important as fundamental elements that determine the overall stiffness of the structure. The SFT segment model, made of a 3-inch (76 mm) diameter tube with a length of 700 mm, was installed at a depth of 1/6 z below the water surface. The parameters tested included the effect of the mooring cable angle (variations: 15°, 30°, and 45°) and the effect of the tube mass (variations: 0.5 kg, 0.75 kg, and 1 kg). The displacement response of the specimens was obtained from video recordings and analyzed using video tracking software. The experimental results show that an increase in the angle of inclination of the mooring cable leads to an increase in stiffness (?) and a smaller structural displacement. In addition, a larger tube mass results in a greater displacement. The experimental data showed good agreement with the theoretical model of single-degree-of-freedom (SDOF) damped forced vibration, with deviations below 10%. Therefore, this study recommends the use of the largest feasible mooring angle and smallest practical tube mass for optimal SFT design, while still considering real-world application limitations.